Answer:
A rational expression is an expression of the form a/b. If we want at least one x in the denominator, we can write the following
![(x-1)/(x-5)](https://img.qammunity.org/2023/formulas/mathematics/college/nvfj3v173ye0ny13tw4krkz83oom8s0ea3.png)
Part a.
If we make the expression equal to 0 and we solve, we get:
![\begin{gathered} (x-1)/(x-5)=0 \\ \\ x-1=0(x-5) \\ x-1=0 \\ x=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2eowcg5xa82n9gi2hnapa19juakw4lkn5o.png)
So, it has a solution because the numerator is equal to 0 when x = 1 and x = 1 doesn't make the denominator equal to 0.
Part b.
If we make the expression equal to y, we get:
![y=(x-1)/(x-5)](https://img.qammunity.org/2023/formulas/mathematics/college/qtx6kgc62009apx20xvwpoyjwyz3j4uz7o.png)
Then, the graph of the expression is
So, the expression doesn't have a value for x = 5 and it doesn't have a value of x that makes y = 1.
Part c.
The expression doesn't have a value for x = 5 because the denominator is equal to 0 at x = 5 and it doesn't have a value of x that makes y = 1 because there is no solution to the equation
![(x-1)/(x-5)=1](https://img.qammunity.org/2023/formulas/mathematics/college/xct6hype3ocjdp7cw8vnbamcny6oc3l244.png)
Part d.
If we add 6 to the denominator, we get the following expression
![y=(x-1)/(x-5+6)=(x-1)/(x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/rux3apphwvjpch65m7l3bhyxcchtc1o9tq.png)
Then, the graph is
Therefore, we can see that the vertical asysmptote change from x = 5 to x = -1 because the denominator change from x = -5 to x = 1.